Gaya Komunikasi Politik dan Tantangan Kepemimpinan Kepala Daerah: Analisis Dua Tahun Kepemimpinan Bupati Majalengka - Syamsul Arif Billah (Universitas Majalengka, 2026)
This study aims to analyze the political communication style of a regional head and to identify the leadership challenges that emerged during the first two years of the Regent of Majalengka’s administration. The research focuses on how the leader’s communication style is constructed in media coverage and its implications for legitimacy and leadership effectiveness at the local government level. A qualitative approach was employed using content analysis of online media reports published over the two-year leadership period. Data were collected through documentation and analyzed using thematic categorization to identify dominant communication patterns, media framing, and emerging perceptions. The findings reveal that the political communication style is predominantly humanistic-participatory, emphasizing emotional proximity, direct engagement with citizens, and persuasive messaging. This approach contributes to strengthening symbolic legitimacy; however, it also encounters challenges related to message consistency and perceived policy effectiveness. Media framing plays a significant role in shaping public interpretations of leadership performance. The study underscores the importance of integrating relational communication strategies with structured and transparent policy communication to enhance leadership effectiveness in local governance.